Measurements of polyethylene terephthalate surface changes after UV exposure and biofilm growth - Isabel Goßmann; Hery Mitsutake; Julius Degenhardt; Morten E Simonsen; Fan Liu (PANGAEA, 2025)
This data set contains data for the characterization and analysis of the surface of a polyethylene terephthalte (PET) drinking bottle and the effects of biofilm and UV exposure on the surface properties. This publication contains data from μ-Raman spectroscopy, atomic force microscopy (AFM), water and diiodomethane contact angles, and surface free energy. Measurements were conducted on pristine PET, biofilm affected PET, UV exposed PET, and biofilm affected + UV exposed PET to determine which parameter induces the strongest changes in surface chemistry.